Application of Linguistic Expertise by Linguistics in Handling Cases of Hate Speech Crimes (Hate Speech) - Nisa Islami, Andi Chenning; Kurniawan, Yunan Prasetyo (Jurnal Indonesia Sosial Sains, 2025)
The rapid development of information and communication technology has significantly transformed global social interactions and human civilization. While it provides numerous benefits, it also gives rise to various issues, including criminal acts such as hate speech. Hate speech, often associated with defamation, is a form of language crime regulated under the Criminal Code and the Law on Electronic Information and Transactions (ITE Law). This study examines the role of linguistic expertise in addressing hate speech crimes, particularly how linguists can contribute to identifying and analyzing the linguistic elements involved in these cases. This research uses a normative juridical approach to examine secondary data, including relevant laws and forensic linguistics literature. The findings indicate that linguistic analysis plays a critical role in determining the guilt or innocence of individuals involved in hate speech crimes in the judicial process. Linguists provide essential assistance in understanding the context and implications of speech, helping law enforcement effectively address hate speech issues. The study concludes that continued application and development of linguistic expertise are vital in improving the handling of hate speech cases and ensuring fair and accurate legal proceedings.